Strategi Komunikasi Public Relation Dalam Membangun Citra Dan Kepercayaan Calon Jemaah Haji dan Umroh - Isma Ismaulidina; Effiati Juliana Hasibuan; Taufik Wal Hidayat Wal Hidayat (Universitas Medan Area, 2020)
The Purpose of this tudy is to study public communication strategy to build image and trust of prospective Jemaah hajj and umroh at PT. Siar Tour Medan. This study has been motivated because the implementation of the hajj and umroh so far ineffectice and inefficient. It has influenced service quality to customers. Methode that used in this stdy is qualitative and used descriptive analysis technique. This study used public relation by RUSLAN Theory known as PENCILS and the image that created through fourth components explain by SOleh Soemirat and Elvinaro Ardianto in the book dasar-dasar Public Relation such as perception, cognition, motivation and attitude.